2023
DOI: 10.1101/2023.04.18.537377
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A critical role for CaMKII in behavioral timescale synaptic plasticity in hippocampal CA1 pyramidal neurons

Abstract: Behavioral timescale synaptic plasticity (BTSP) is a type of non-Hebbian synaptic plasticity reported to underlie place field formation in the hippocampal CA1 neurons. Despite this important function, the molecular mechanisms underlying BTSP are poorly understood. The αCalcium-calmodulin-dependent protein kinase II (αCaMKII) is activated by synaptic transmission-mediated calcium influx and its subsequent phosphorylation is central to synaptic plasticity. Because the activity of αCaMKII is known to outlast the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It was recently confirmed that BTSP is expressed by changes in synaptic efficacy between CA3 and CA1 neurons in vivo 42 . BTSP also requires CaMKIIa signaling, suggesting that canonical LTP expression mechanisms may underlie BTSP 48,49 . Our work extends these findings and demonstrates that full expression of BTSP may require specific membrane fusion proteins implicated in regulated GluA1(+) AMPAR exocytosis.…”
Section: Enriching and Stabilizing Hippocampal Place Codes Through St...mentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently confirmed that BTSP is expressed by changes in synaptic efficacy between CA3 and CA1 neurons in vivo 42 . BTSP also requires CaMKIIa signaling, suggesting that canonical LTP expression mechanisms may underlie BTSP 48,49 . Our work extends these findings and demonstrates that full expression of BTSP may require specific membrane fusion proteins implicated in regulated GluA1(+) AMPAR exocytosis.…”
Section: Enriching and Stabilizing Hippocampal Place Codes Through St...mentioning
confidence: 99%
“…Second, sequences of place cells that were active during exploration are stabilized through plasticity during offline reactivation events referred to as sharp-wave ripples (SWRs) -high frequency local field potential (LFP) events in which the same sequences of place cells are reactivated at highly compressed speeds [45][46][47] . Though the molecular underpinnings of BTSP and SWR-induced plasticity are a topic of increasing interest, the mechanisms for expressing either form of plasticity remain a mystery 38,[48][49][50][51][52] .…”
Section: Introductionmentioning
confidence: 99%